Composing of Lead Time Reduction Approach in Assembling an Electrical Product - Intan Bazliah, Mohd; Abdullah, Ibrahim (Penerbit Universiti Malaysia Pahang, 2016)
The paper explores the lead time reduction projects that have been implemented in an electrical product assembly line, called subwoofer speaker. Observation has been conducted on 26 workstations which are involved in an assembly line. Group discussion, real-time study, and action research have been performed to reduce cycle time. The result shows that most ideas are able to reduce cycle time to as minimum as 0.1 seconds from the original cycle time. In other words, the project is able to give an impact of at least 520 seconds on daily normal working hours. Besides, it also enhances the participation of the employee in reducing lead time while improving production capacity